Look beautiful but be aware: the hidden dangers of cosmetics - Jallad, Karim (2014)
This review article summarizes the most recent published data pertaining to heavy metals content in different cosmetic products. Most of the cosmetic products such as lip gloss, mascara, foundation, blush, cream, blush, eye shadow, eyeliner etc. tested, contained different levels of heavy metals. The highest concentrations of heavy metal namely arsenic, cadmium, and lead were detected in lipsticks and lip glosses. The low concentrations of heavy metals measured in the different investigated products were reassuring; however, since they are used repeatedly and daily, the cumulative effects of prolonged heavy metals exposure may be of concern. Thus, the use of cosmetic products containing impurities such as heavy metals especially among children may constitute a public health risk.